Perancangan User Interface melalui Pengembangan Wireframe pada Pengelolaan Zakat dan Sedekah Digital - Fata Nidaul Khasanah; Dhian Tyas Untari; Fauzan Natsir (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2026)
The rapid advancement of digital technology has transformed various public service sectors, including the management of zakat and charitable donations in mosques. However, many mosques still rely on conventional management practices, which often result in administrative inefficiencies, limited financial transparency, and suboptimal transaction data management. Therefore, a digital zakat and charity management system is needed to improve service quality and accountability. This study aims to design a wireframe as an initial step toward developing a comprehensive user interface for a digital zakat and charity management system based on user needs. A qualitative descriptive approach was employed, emphasizing user-centered requirements analysis. The research process involved understanding the user context and defining user requirements. The findings identified two primary user groups, namely donors (muzakki) and zakat management administrators, along with their respective pain points. Based on these findings, system requirements and proposed solutions were formulated, followed by the design of user flows and low-fidelity wireframes. The resulting wireframe includes key features such as a zakat and charity management dashboard, donation and zakat payment services, and financial reporting modules. These designs provide a foundation for developing a user-centered digital management system for mosque-based zakat and charity services.